Tingkat Pengetahuan Petani terhadap Pascapanen Jagung Hibrida (Kajian Kritis Tahapan Pascapanen di Kabupaten Gowa) - Rahmadana Rahmadana; Akbar Akbar; Syafiuddin Saleh (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Post-harvest handling is an important part of agribusiness development because it plays a role in maintaining quality, reducing yield losses, and adding value to products. This study aims to determine the level of farmers' knowledge in handling hybrid corn post-harvest in Baturappe Village, Biringbulu District, Gowa Regency. This study uses two types of data, namely primary data and secondary data. Primary data were collected through direct interviews with all respondents using a pre-designed questionnaire and through field observations. Meanwhile, secondary data were obtained from literature, libraries, and relevant agencies such as the Baturappe Village Office. Sampling was conducted using simple random sampling with 15 respondents from a population of 150 farmers. The results showed that the level of knowledge of corn farmers in Baturappe Village regarding post-harvest handling, which includes the stages of shelling, drying, packaging, and storage, had an average score of 54, which is classified as high. This indicates that farmers have a good understanding of corn post-harvest handling procedures. Overall, the farmers' level of knowledge, attitude, and skills were in the very high category in terms of corn farming management in the region. Each aspect of the farmers' behavior showed varying degrees of understanding, but remained in the high category.